1998
DOI: 10.1016/s0925-4773(98)00021-5
|View full text |Cite
|
Sign up to set email alerts
|

Anterior specification of embryonic ectoderm: the role of the Xenopus cement gland-specific gene XAG-2

Abstract: In a search for novel developmental genes expressed in a spatially restricted pattern in dorsal ectoderm of Xenopus we have identified XAG-2, a cement gland-specific gene with a putative role in ectodermal patterning. XAG-2 encodes a secreted protein, which is expressed in the anterior region of dorsal ectoderm from late gastrula stages onwards. Activation of XAG-2 transcription is observed in response to organizer-secreted molecules including the noggin, chordin, follistatin and cerberus gene products. Overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
129
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(134 citation statements)
references
References 68 publications
5
129
0
Order By: Relevance
“…AGR2 was originally identified as a potential secretory protein that is highly expressed in frog eggs (Aberger et al, 1998). The human AGR2-coding sequence is located on chromosome 7p21, well known as a locus of frequent genetic alterations (Petek et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…AGR2 was originally identified as a potential secretory protein that is highly expressed in frog eggs (Aberger et al, 1998). The human AGR2-coding sequence is located on chromosome 7p21, well known as a locus of frequent genetic alterations (Petek et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Anterior gradient 2 (AGR2) homolog expression is responsible for the development of the cement gland, a glandular organ in frog embryos, and for limb regeneration in newts. 7,8 In humans, the AGR2 gene lies at chromosomal position 7p21.3, and gives rise to an 18-kDa-sized protein. AGR2 is classified as a member of the protein disulfide isomerase family, involved in protein maturation and folding, on the basis of structural similarity.…”
mentioning
confidence: 99%
“…XAG-1 and XAG-2 are expressed in ectodermal cells during the development of the cement gland, a mucus-secreting organ in the head that is involved in the attachment of the frog embryo to a solid support (Sive et al, 1989). Indeed, the finding that XAG-2 is involved in the regulation of dorsoanterior ectodermal cell fate during cement gland differentiation (Aberger et al, 1998) suggests its potential role as a differentiation factor. hAG-2 and hAG-3 each have a predicted N-terminal cleavable secretory signal sequence (http:// psort.nibb.ac.jp) and we previously demonstrated that hAG-3 was localised to endosomes in the T47D breast cancer cell line, further evidence that it is a secreted protein (Adam et al, in Press).…”
mentioning
confidence: 99%